2021
DOI: 10.1186/s13046-021-01920-y
|View full text |Cite
|
Sign up to set email alerts
|

NLRP7 deubiquitination by USP10 promotes tumor progression and tumor-associated macrophage polarization in colorectal cancer

Abstract: Background NOD-like receptors affect multiple stages of cancer progression in many malignancies. NACHT, LRR, and PYD domain-containing protein 7 (NLRP7) is a member of the NOD-like receptor family, although its role in tumorigenesis remains unclear. By analyzing clinical samples, we found that NLRP7 protein levels were upregulated in colorectal cancer (CRC). We proposed the hypothesis that a high level of NLRP7 in CRC may promote tumor progression. Here, we further investigated the role of NLRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 49 publications
(30 reference statements)
2
33
0
Order By: Relevance
“…USP10 has been found to mediate deubiquitination and upregulation of the NLR family pyrin domain containing 7 to promote M2 polarization of macrophage and tumor progression in colorectal cancer. 33 In relation to the role of the USP10/YAP1 axis in immune escape and malignant development in PAAD, we first examined the PD‐L1 and galectin‐9 levels in cells. As aforementioned, PD‐L1 plays a critical role in the potential of cancer cells to evade the host’s immune system.…”
Section: Discussionmentioning
confidence: 99%
“…USP10 has been found to mediate deubiquitination and upregulation of the NLR family pyrin domain containing 7 to promote M2 polarization of macrophage and tumor progression in colorectal cancer. 33 In relation to the role of the USP10/YAP1 axis in immune escape and malignant development in PAAD, we first examined the PD‐L1 and galectin‐9 levels in cells. As aforementioned, PD‐L1 plays a critical role in the potential of cancer cells to evade the host’s immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Both RSL3 (5 mg/kg) and cetuximab (13 mg/kg) were administered by intraperitoneal injection in a volume of 100 μl once per day. The tumour volume was calculated as 0.5 × length × width 2 [ 50 ]. After 17 days of treatment, the mice were sacrificed, and the tumours were removed.…”
Section: Methodsmentioning
confidence: 99%
“…These differences suggested heterogeneity between cancers that recruit APCs to the TME. A recent study showed that USP10 promotes tumor progression and TAM polarization in colorectal cancer ( 18 ). Therefore, our results revealed that USP10 might regulate TAM polarization.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, USP10 is closely associated with tumor immunity. USP10 has been identified to be involved in metastasis and can drive tumor-associated macrophage polarization in colorectal cancer ( 18 ). Depletion of USP10 markedly reduced apoptosis and immune cell infiltration ( 19 ).…”
Section: Introductionmentioning
confidence: 99%